Dual-Chamber Microbial Fuel Cell for Bioelectricity Generation Using Coastal Sediments: A Case from Kendari Bay - Ahmad, La Ode; Istianandar, Muhammad Iqbal Sya'bani; Wa Ode Novi Haryanti; Zaeni, Ahmad; Alwahab; Yunus, La Ode Ichlas Syahrullah; Husaeni, Yusuf Ahmad; Robby Sudarman (Advance Sustainable Science Engineering and Technology, 2025)
This study evaluates the potential of Kendari Bay sediment as an alternative source of electrical energy through the dual-chamber Sediment Microbial Fuel Cell (SMFC) technology. The research focused on sediment characterization, performance analysis using an aerator and KMnO₄, post-operation substrate changes, and the identification of electrogenic bacteria. The results showed that the sediment contained 43.24% moisture, 4.23% organic carbon, 1.08% total nitrogen, a C/N ratio of 3.92, pH 7.38, and conductivity of 11.56 mS. The SMFC generated a voltage of 0.404 V (aerator) and 1.628 V (KMnO₄), along with a current of 5.0 µA. After SMFC operation, organic content decreased, with 42.65% moisture, 4.06% organic carbon, 0.97% total nitrogen, a C/N ratio of 4.19, pH 7.86, and conductivity of 15.78 mS. Identified bacteria were Gram-positive Bacillus spp. These findings demonstrate that aerator and KMnO₄ application in dual-chamber SMFC significantly enhance energy conversion efficiency using marine sediment.